Evaluation of the Lean Approach Implementation in Engineering Education - Amine Hadek; Soumia Bakkali; Souad Ajana (Emerging Science Journal, 2023)
This study aims to study the benefits of lean approach implementation in engineering education in Morocco by using three concrete case studies to present a comparative analysis between situations with and without Lean approach deployment. The first project focuses on improving internet access. The second project aims to improve the conduct of practicum sessions. The third project aims to identify and improve the performance of the processes implemented in the student affairs department. In this research study, deductive methodology is followed, also called the "hypothetical-deductive approach", First, we presented a synthetic analysis of Lean implementation studies existing in the literature between 2000-2023, then we presented three Lean implementation projects in the engineering school in Morocco. This research work allowed us to present, with concrete cases, the contribution of the approach to engineering education in Morocco, whether it is in the teaching processes or in the support and management processes within an engineering school. The involvement and sensibilization of the resources represent key success factors of this Lean transformation. This research work can serve as a baseline reference for other Lean implementation initiatives in the field of education in Morocco. On the one hand, while examining the literature, we found a scarcity of studies that have presented a comparison between the situation without and with the Lean approach. On the other hand, the Lean approach is a new concept that has never been discussed concretely in the context of Moroccan engineering; the present research fills that gap. Doi: 10.28991/ESJ-2023-07-04-07 Full Text: PDF